(NuKRA)QÇNOMOWNA KNIGA(B, 1798-1916 :s)E (NB)QÆBLÆOGRAFÆ^NIJ POKAV^IK (B/s)E (NwIP(B. 1,s <1798=(NtISQ^A S)QÆMSOT DEW(B'(NQNOSTO WOSXMIJ(B> - <1885=(NtISQ^A WÆSÆMSOT WÆSÆMDESQT P(B'(NQTIJ(B> / (NREDAKTOR w(B. (N`(B. (NoMELX^UKs)E - (NoMELX^UK(B, (Nw(B. (N`(B.,s; (NoNI]ENKO(B, (No(B. (Ns(B.,s; (Nb)QÃLQÃWA(B, (Nl(B. (Nw(B.,s)E; (NbROWK)QÆN(B, (Na(B. (Ng(B.,s)E; (NdUBROW)QÆNA(B, (Nl(B. (Na(B.,s)E ((NkI)QÇW (B:s)E (NaBRIS(B,s, 1996)
[(NpOKAV^IK DA)QÃ WÆDOMOSTÆ PRO NAQWNÆSTX KNIG UKRAÇNSXKO@ MOWO@ ZA PERÆOD (B1798-1885 (NRR(B.].s)E
)Qæ(NM(B. (NPOKAV^(B.: (NS(B. 151-177. - (NpOKAV^(B. (NNAZW(B: (NS(B. 178-197s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NnAC)QÆONALXNA BÆBLÆOGRAFÆQ UKRAÇNSXKAs)E; (NPOKAV^IKs; (NKNIGI UKRA)QÇNSXKÆs)E